People's experience and facts of changing climate: impacts and responses. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – This paper aims to explore the local knowledge on climate change, its impacts and the responses they are making at the household or community level to deal with the changes on the basis of their experiences and perceptions.Design/methodology/approach – The study was based on household survey conducted with one male and one female respondent in 202 households. Alongside, series of focused group discussions were conducted with local people to capture the perception on about climate change, its impacts and adaptation strategies applied to enhance their resilience capacity to changing climate. Rainfall and temperature data were collected from Department of Hydrology and Meteorology (DHM) for seven and four different stations, respectively, within Kathmandu Valley and analyzed to understand the climatic trend.Findings – The perception of most of the local people on changes in temperature was almost in line with the recorded long‐term climatic trend both showing an increasing trend, whereas the perception of decreasing both monsoon and non‐monsoon rainfall did not match with the recorded data as the rainfall data analysis did not reflect any clear long‐term pattern. People have been facing several impacts such as decrease in water sources, decrease in agricultural crop production, increase in new crop pest and weeds in agricultural crops. Local people are responding to these impacts as per their own skills and traditional knowledge.Originality/value – This is totally original research article and the impacts and adaptations measures documented in this article may represent the case of peri‐urban areas of least developed countries like Nepal. Acknowledgements : The paper is based on the findings of action research project on Water Security in Peri‐urban South Asia: Adapting to Climate Change and Urbanization implemented in peri‐urban areas of Kathmandu Valley by Nepal Engineering College in coordination with South Asia Consortium for Interdisciplinary Water Resource Studies (SaciWATERs) with financial support of International Development Research Centre (IDRC), Canada.